Recall Referendum sebagai Alternatif Proses Penggantian Antarwaktu Lembaga Legislatif di Indonesia - Muhammad Irfan Hilmy; Trian Marfiansyah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to provide democratic ideas related to the Intertemporal Replacement process and to find out about its less democratic practices so far. The research method used in this article is a normative juridical research method, with a statutory, case and conceptual approach. The purpose of this discussion is to analyze a memory process which is more democratic and more appropriate for application in Indonesia and to identify recall practices in Indonesia. The result of this study is that the recall process given to political parties only makes the recall instrument a tool for political parties in controlling their members in the legislative body as well as to scare their members who are against the policies of political parties. Things like this certainly hinder the development of democracy in the institutional system in Indonesia. This is shown from several recall cases which only for reasons contrary to political parties then expel their members from membership in the legislature. To change this practice, in this study, an interim replacement mechanism with a referendum recall process was initiated to involve the people in the process of dismissing members of the legislature so as to maintain the interests of political parties to remain democratic and prevent interim replacements from being used as weapons to frighten legislators. With the recall of the referendum, the people will be fully involved in the recall process so that the process becomes more transparent and democratic.